″The role of communication competence in the professional activity of specialists in the educational sphere″ - Vasylieva, M. P. (Problems of Engineer-Pedagogical Education, 2018)
The article studies communication as the main instrument that is used by educators whilst performing their professional pedagogical functions. Some general and specific features of such concepts as ―interaction‖ and ―communication‖, which are highly interconnected in the teaching and learning process, are defined. Professional pedagogical communication, the core of which is the process of interaction between the parties, is characterized in the article. Pedagogues play the main role in this process. As communication is pedagogues‘ main type of activity and one of the constituent parts of the educational process, the aspects of professional pedagogical interaction are characterized. The importance of communication culture of specialists in the educational sphere and communication competence as its ground is substantiated. The elements of communication competence of a specialist in the educational sphere are defined basing on the classification of professional pedagogical communication skills provided by the scholars. The defined skills should be formed through specially organized activities during vocational training of future specialist and by means of self-development.